1953
DOI: 10.1139/f53-019
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Growth of Phytoplankton

Abstract: In reviewing the literature dealing with the influence of physical, chemical and biochemical factors on the development and decline of phytoplankton pulses, this paper first outlines the seasonal cycle of phytoplankton pulses which occurs in many parts of North America and then presents evidence that this cycle is caused chiefly by the seasonal change in water temperatures resulting from the change in solar radiation. The way in which this cycle is sometimes obscured by irregular changes in phytoplankton numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

1955
1955
1985
1985

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…The low standing crop of the phytoplankton was nonetheless related to low nutrient levels. For example, the concentration of NO,-N and SiO, fell well outside of the optimal range reported for a number of planktonic species (McCombie 1953;Shapiro and Glass 1975 densities many times greater than those recorded in this study (Silva and Papenfuss 1953).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The low standing crop of the phytoplankton was nonetheless related to low nutrient levels. For example, the concentration of NO,-N and SiO, fell well outside of the optimal range reported for a number of planktonic species (McCombie 1953;Shapiro and Glass 1975 densities many times greater than those recorded in this study (Silva and Papenfuss 1953).…”
Section: Discussionsupporting
confidence: 50%
“…These authors found that appreciable quantities of Na and K are required for extensive development of Cyanophyta. Perhaps utilization of Na and K was restricted by the low levels of other cations, particularly Mg as discussed by McCombie (1953).…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of seasonal succession of the dominant groups of algae is generally similar to that common to many other moderately eutrophic lakes and reservoirs in temperate lowlands (e.g. Vetter, 1937;McCombie, 1953;Rodhe, Vollenweider & Nauwerck, 1958;Ridley, 1970), but there are several points of difference in detail. The most notable of these are the earlier commencement of the spring increase, the relative paucity of Chrysophyceae, and the emergence of diatom populations in early summer.…”
Section: Discussionmentioning
confidence: 51%
“…Many data, both qualitative and quantitative!, have accumulated during the last 20 years (see McCombie 1953, Pennak 1946, and Welch 1935, for bibliographies) on plankton productivity of freshwater areas. Many data, both qualitative and quantitative!, have accumulated during the last 20 years (see McCombie 1953, Pennak 1946, and Welch 1935, for bibliographies) on plankton productivity of freshwater areas.…”
Section: Introductionmentioning
confidence: 99%